2003
DOI: 10.1111/j.0008-3658.2003.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based cooperative ventures for adults with intellectual disabilities

Abstract: When people with intellectual disabilities gain some influence over the running of their own households and the organisation of their workplaces, their lives can improve markedly. But success depends on community support not only from their families and social workers, but also from nonprofit groups and public services such as social housing and public transit. Dominant trends among institutions in the social sector responsible for meeting the needs of people with intellectual disabilities have produced models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Regardless of the labels used, group‐orientated activities within centres continue, which many would argue are exploitative, closed, paternalistic and preventive of proper community integration (Kirby 1986; Murphy and Rogan 1995; Parent et al . 1989; Neufeldt 1990; Schuster 1990 as cited in Lemon & Lemon ). Others claim, by contrast, that rather than simply being physically integrated within the general community, service provision should be concerned with connectedness and that such connectedness is actually more achievable within a community of people with an intellectual disability (Cummins & Lau ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the labels used, group‐orientated activities within centres continue, which many would argue are exploitative, closed, paternalistic and preventive of proper community integration (Kirby 1986; Murphy and Rogan 1995; Parent et al . 1989; Neufeldt 1990; Schuster 1990 as cited in Lemon & Lemon ). Others claim, by contrast, that rather than simply being physically integrated within the general community, service provision should be concerned with connectedness and that such connectedness is actually more achievable within a community of people with an intellectual disability (Cummins & Lau ).…”
Section: Discussionmentioning
confidence: 99%
“…The study evaluated and resolved the implication of topical work on disability within human geography as a whole and suggested possible links to the growing literature on rights, social justice, and ethics. Lemon and Lemon [3] reported that the potential of intellectual special needs people can noticeably improve and imply in managing their households and the workplaces. The study affirmed that the success of such an economic model can happen with community support viz., families, social workers, and from non-profit groups and public services such as social housing and public transit.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, supported work in a segregated setting, i.e. sheltered work, may serve as a meaningful activity and a way to earn money (Butcher & Wilton, 2008;Hall, 2010), but is also blamed for resulting in exploitation (Hyde, 1998;Lemon & Lemon, 2003) and for perversely bringing about social segregation and stigmatization (Holmqvist, 2010;Sebrechts et al, 2018). Therefore, alternative routes are being explored to socially include these vulnerable groups through work (Hall & Wilton, 2011).…”
Section: Introductionmentioning
confidence: 99%